Relationship between disease severity and inflammatory markers in cystic fibrosis. Issue 6 (December 1996) - Koller, D Y; Götz, M; Wojnarowski, C; Eichler, I
Abstract : To evaluate the clinical use of measuring neutrophil, lymphocyte, and eosinophil activities, serum myeloperoxidase (MPO), soluble interleukin-2 receptors (sIL-2R), and eosinophil cationic protein (ECP) were measured in 98 patients with cystic fibrosis and in 85 healthy children. Serum concentrations of MPO, sIL-2R, and ECP were increased in patients with cystic fibrosis (median 807 micrograms/l, 4452 pg/ml, 48.8 micrograms/l, respectively) compared with the controls (median 319 micrograms/l, 2743 pg/ml, 9.4 micrograms/l). ECP concentrations, but not serum MPO or sIL-2R, were significantly related to disease severity assessed by the Shwachman-Kulczycki score and by pulmonary function (forced expiratory volume in one second % predicted). Neither ECP nor sIL-2R was influenced by Pseudomonas aeruginosa infection, acute pulmonary exacerbation, or atopy. Serum MPO, however, was strongly correlated with acute pulmonary exacerbation. In the light of these findings the measurement of serum ECP might thus be used for clinical monitoring and for assessing disease severity in cystic fibrosis. The measurement of serum MPO and sIL-2R did not correlate with the disease severity.